2007
DOI: 10.1139/w07-078
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting highly diverse endophytic Pestalotiopsis spp. with antibacterial properties from Maytenus ilicifolia, a medicinal plant from Brazil

Abstract: Thirteen endophytic fungal strains of the genus Pestalotiopsis were isolated from the medicinal plant Maytenus ilicifolia Mart. ex. Reiss (commonly known as "espinheira santa") and their antimicrobial properties were investigated. Two isolates were successful in inhibiting the growth of the tested microorganisms (Escherichia coli, Klebsiella pneumoniae, Micrococcus luteus, Staphylococcus aureus, and methicillin-resistant Staphylococcus aureus (MRSA)) using the technique of bioautographic thin-layer chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
6
0
3
Order By: Relevance
“…Other studies analyzing the interactions between endophytic isolates and different pathogens demonstrated a reduction in pathogens growth ranging from 28.5 to 78.8% (Gomes-Figueiredo et al, 2007;Campanile et al, 2007;Sempere andSantamarina, 2007, Bailey et al, 2008). Crozier et al (2006), also studying the phytopathogens Moniliophthora roreri and M. perniciosa, the causative agents of fresh green bean rot and witches' broom disease, respectively, used endophytic fungi to combat pathogens and showed that the endophytic fungi of this plant could prevent the initial colonization of the pathogens competing for the same ecological niche and invading them.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies analyzing the interactions between endophytic isolates and different pathogens demonstrated a reduction in pathogens growth ranging from 28.5 to 78.8% (Gomes-Figueiredo et al, 2007;Campanile et al, 2007;Sempere andSantamarina, 2007, Bailey et al, 2008). Crozier et al (2006), also studying the phytopathogens Moniliophthora roreri and M. perniciosa, the causative agents of fresh green bean rot and witches' broom disease, respectively, used endophytic fungi to combat pathogens and showed that the endophytic fungi of this plant could prevent the initial colonization of the pathogens competing for the same ecological niche and invading them.…”
Section: Discussionmentioning
confidence: 98%
“…Endophytic fungi inhabiting plants with a well-established ethnobotanical history represent a unique ecological group, since the medicinal effects of the plant could also be related to the resident endophytes (Kusari, Pandey, et al 2013). In the last 10 years, there has been an upsurge of studies that have targeted fungal endophytes from medicinal plants for the isolation and characterization of novel metabolites (Wang et al 2002; Tejesvi et al 2006; Gomes-Figueiredo et al 2007; Huang et al 2008; Hyde and Soytong 2008; Naik et al 2008; Krishnamurthy et al 2009; Bills et al 2012; Gond et al 2012; Mishra et al 2012; Vieira et al 2012; Zubek et al 2012; Miller, Qing, Sze, Neilan, et al 2012; Aly et al 2013; Chen et al 2013; Ellsworth et al 2013; Kusari, Kusari, et al 2013). In the present study, we have isolated four new secondary metabolites [biscognin A ( 1 ), biscognin B ( 3 ), monascuskaoliaone B ( 4 ), and epi -pestalamide A ( 6 )] from milk thistle endophytes, in addition to scores of known compounds that are members of a range of different classes of natural products.…”
Section: Discussionmentioning
confidence: 99%
“…They observed strong in vitro cytotoxicity for KB cancer cells (human epidermal carcinoma), as well as for P388 cells (murine leukemia). In a study in Brazil, Gomes-Figueiredo et al (2007) characterized endophytic Pestalotiopsis from Maytenus ilicifolia (espinheira-santa), which showed antimicrobial activity against various human pathogens.…”
Section: Introductionmentioning
confidence: 99%